21st century skills and competences: Challenges with a focus in information and communication - Belluzzo, Regina Celia Baptista[UNESP]; Rosetto, Marcia (IGI Global, 2021)
It is remarkable how quickly social and technological transformations have been occurring since the end of the 20th century, evolving in different stages and subsequently expanded in this 21st century. These changes have been promoting new social and behavioral structures and require different skills and competences to deal with the impacts and challenges that result from them. The chapter presents a brief discussion on the importance and relevance of what skills and competencies are required in the 21st century, the definitions and concepts found in the literature, and proposes a three-dimensional view that consists of the dimensions of information, communication, and ethics and their social impact in the digital world.